MAKNA SIMBOLIS TARI JARO ROJAB DI KECAMATAN WANGON KABUPATEN BANYUMAS - Pravitasari , Galuh Lutfa; Widyawati, Setya (Greget : Jurnal Kreativitas dan Studi Tari, 2024)
This journal examines the dance creations of Banyumasan style, namely Jaro Rojab Dance by Ida Restina. This dance was created to participate in Festival dan Lomba Seni Siswa Nasional (FLS2N) for high school in Banyumas Regency. Although dance creations but there are stories and plots there must be meanings and values expressed through symbols. This is interesting to research, so the problem is formulated as follows: 1. What is the form of Jaro Rojab Dance? 2. What is the symbolic meaning of Jaro Rojab Dance? To explain the problem use the form theory of Sri Rochana Widyastutieningrum, the theory of symbols from Wiryamartana and the theory of Allegra Snyder. The presentation of this research data is a description of the analysis. The results of observations on the form of Jaro Rojab Dance to analyze the symbol which is externally the constituent of Jaro Rojab Dance inspired by the traditional ceremony procession of jaro change in Cikakak Village and the movement of Lengger banyumas art. While internally is the treasury of motion that undergoes stages of stimulation, transformation, unity. Overall, Jaro Rojab Dance is a picture and symbol of the nature of the local community where the dance created. In other side, Jaro Rojab dance also performed the potential of cultural tourism owned by Cikakak Village and Banyumas Regency.